Mechanism of application nursery cultivation arbuscular mycorrhizal seedling in watermelon in the field. (15th November 2018) - Ren, Lixuan; Wang, Bingshuang; Yue, Caipeng; Zhou, Shipin; Zhang, Shuhuan; Huo, Hongwei; Xu, Guohua
Abstract : Arbuscular mycorrhizal fungi (AMF) colonisation of plant root facilitates the absorption of nutrients such as phosphorus (P) and enhances plant biotic and abiotic resistance generally. However, arbuscular mycorrhiza (AM) colonisation decreases with application of chemical fertiliser. Here, we investigated whether AMF inoculation in nurseries would facilitate AM colonisation and take physiological and ecological functions in watermelon ( Citrullus lanatus ) in the field. Pot experiments were carried out to study the change of AMF colonised seedling on physiology and gene expression in nursery site. Field experiments were performed to investigate the effect of nursery AMF inoculation on yield, quality and disease resistance of watermelon in the field. The results showed that nursery‐inoculated seedlings produced more dry matter and root surface area than non‐inoculated seedlings. Expression of the secretory purple acid phosphatase (PAP) genes ClaPAP10 and ClaPAP26 was up‐regulated following AMF colonisation. Accordingly, acid phosphatase activities at the root surface and P concentrations in seedling were enhanced. After transplantation to the field, the shoot dry matter and P concentration in old stem were higher in the nursery AMF inoculated seedlings than that in non‐AMF inoculated seedling. AMF inoculation also induced increase of yields and decrease of wilt disease indexes and soluble sugar content. In addition, acid phosphatase activities and AMF spore densities were increased by nursery‐inoculation in watermelon rhizosphere soil in the field. In conclusion, nursery colonisation AMF seedling enhanced watermelon growth and yield by improving the root growth and P acquisition in nursery cultivating stage, as well as optimised soil properties in the field. Nursery cultivation of watermelon seedling with AMF was an effective technique to reduce wilt disease in continuous cropped management in watermelon. Abstract : Mechanism of nursery cultivation arbuscular mycorrhizal seedling acting on watermelon production.